Effect of a Single Intravesical Instillation of Mitomycin C on the Intravesical Recurrence Rate After Ureteroscopy for Upper Tract Urothelial Carcinoma: The SINCERE Prospective Multicenter Registry Study - Orlane Figaroa; Ranan Dasgupta; Nora Hendriks; Guido Kamphuis; Jorg Oddens; Jeroen van Moorselaar; Adriaan Bins; Joyce Baard (European Urology Open Science)
Background: Upper tract urothelial carcinoma (UTUC) is a rare malignancy, accounting for 5–10% of all urothelial carcinomas (UCs). Radical nephroureterectomy (RNU) has been the standard treatment, but kidney-sparing surgery (KSS) via ureteroscopy (URS) is now recommended for low-risk cases. KSS is associated with a higher rate of intravesical recurrence (IVR). The SINCERE study is evaluating whether a single postoperative intravesical instillation of mitomycin C (SI-MMC) after URS can reduce the IVR rate. Study design: This is a prospective multicenter registry study enrolling patients with nonmetastatic UTUC undergoing URS followed by SI-MMC. Data will be compared to a historical control cohort without adjuvant MMC. Patients are aged ≥18 yr with no history of bladder cancer or contralateral UTUC. The study is following the principles of the Declaration of Helsinki and has received ethics approval. Primary and secondary outcomes: The primary outcome is total IVR and time to IVR. The secondary outcome is evaluation of predictive variables for IVR in patients with UTUC after endoscopic treatment. Discussion: Given the high recurrence rate after URS, the study aim is to provide evidence regarding MMC use to reduce IVR and address the current lack of robust data for this strategy. The study has potential to change clinical practice by demonstrating the efficacy of SI-MMC in preventing IVR after URS for UTUC.